Demonstrating the requirements for new reference ranges for diagnosis and prognosis to reflect subsets of the population. (30th January 2019) - Wilson, Helen
Abstract: Reference ranges (RRs) are not produced for different subsets of the population, other than for gender. This study aimed to explore the impact of generalised RRs on diagnosis thus proving the necessity for new RRs taking into account different ethnicities (hispanic, white, black and Asian). This impact was explored by direct comparisons of RRs produced for different ethnicities in which significant differences would provide evidence for possible misdiagnosis. This was achieved by creating RRs from the National Health and Nutrition Examination Survey, a programme of studies assessing the health and nutritional status of children and adults within USA. The 2.5th and 97.5th percentiles from the 2013–2014 data was calculated after those deemed unhealthy were removed via a set of extensive parameters. Having bootstrapped the data 30 times, a Kruskal–Wallis statistical test was performed followed by a Mann–Whitney post hoc . Nearly all male lower and upper limits were found to be significantly different to each other, apart from the upper limits of hispanic to both white and black, and white to black. Female results showed almost an equal amount of significant and non-significant differences. Those which were significantly different were the upper and lower limits of all the ethnicities to Black, alongside the lower limits of White to Asian. The results of this study suggest that a proportion of misdiagnosis could be avoided if separate RRs were produced, at least for different ethnicities.